UDASH – Unified Database for Arctic and Subarctic Hydrography - Behrendt, Axel; Sumata, Hiroshi; Rabe, Benjamin; Schauer, Ursula (Earth System Science Data, 2018)
UDASH (Unified Database for Arctic and Subarctic Hydrography) is a unified and high-quality temperature and salinity data set for the Arctic Ocean and the subpolar seas north of 65◦N for the period 1980–2015. The archive aims at including all publicly available data and so far consists of 288 532 oceanographic profiles measured mainly with conductivity–temperature–depth (CTD) probes, bottles, mechanical thermographs and expendable thermographs. The data were collected by ships, ice-tethered profilers, profiling floats and other platforms. To achieve a uniform quality level, suitable for a wide range of oceanographic analyses, approximately 74 million single measurements of temperature and salinity were thoroughly quality checked. A large number of duplicate and erroneous profiles were detected and not included in the archive. Data outliers were flagged for quick identification. The final archive provides a unique and simple way of accessing most of the available temperature and salinity data for the Arctic Ocean and can be downloaded from https://doi.pangaea.de/10.1594/PANGAEA.872931.